Social Capital, Knowledge Sharing, Innovation, and Performance of Coffee Producer SMEs in Purworejo, Central Java - Mifta Khurrohmah; Yuli Liestyana; Tri Wahyuningsih (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Indonesian SMEs compete globally for profits, market share, and needed resources. However, the performance of SMEs can be influenced by current economic conditions, the Covid-19 pandemic has caused SME revenue turnover to decline due to economic constraints, a decrease in people's purchasing power, and the power of online marketing not maximized. The solutions that come to mind are the development of social capital, knowledge sharing, and applying innovation in business operations. This study aimed to determine whether social capital, knowledge sharing, and innovation have a direct or indirect effect on the performance of SMEs, especially in the coffee industry in Purworejo Regency, Central Java. Respondents in this study were 33 SMEs of the coffee industry in Purworejo, Central Java. Data were obtained from questionnaires and data analysis using the multiple regression method with F test, partial t-test, and coefficient of determination test (R2). The results show that social capital, knowledge sharing, and innovation significantly affect coffee SMEs' performance in the Purworejo industry. In contrast, partially, social capital and innovation have a significant effect on the performance of SMEs. On the other hand, knowledge sharing has no significant effect on the performance of SMEs.